Ocular manifestations of pregnancy and labour: from the innocuous to the sight threatening. (6th July 2020) - Patil, Ajay D; Ellabban, Abdallah A; Patil, Dilip B; Yorston, David; Williamson, Thomas H; Laidlaw, David A; Vize, Colin J; Hingorani, Melanie; Morris, Edward P
Abstract : Key content: Pregnancy may precipitate several physiological changes that can have ocular consequences; many of these are innocuous and require little more than reassurance for the patient. There are uncommon instances of new sight‐threatening pathology that necessitate a prompt approach. Pregnant women presenting to the ophthalmologist with ocular symptoms can cause concern because alternative differentials may need to be considered; and the potential teratogenic or fetotoxic effects of investigations or treatment mean that management decisions may, in some cases, differ to those of the nonpregnant patient. Learning objectives: To be aware of both physiological and pathological ocular changes that may occur during pregnancy. To develop a greater understanding of investigations and management of ophthalmic and neuro‐ophthalmic disorders in pregnancy. To develop an understanding of referral pathways, enabling an optimal outcome for both mother and baby.